PEMANFAATAN STYROFOAM SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS PADA BETON DENGAN FAS 0.4 - Danindra Pramudya Wardana; Gilang Fadhlurrahman Evriantama; Muhtarom Riyadi (Construction and Material Journal, 2021)
Concrete is a material commonly used for structural work. However, concrete has one disadvantage, namely that its specific gravity is high enough so that the dead load on a structure becomes large. One way to deal with high concrete density is to use Styrofoam waste as a substitute for some of the fine aggregate. This research was conducted to examine the physical and mechanical properties as well as the optimum value of compressive strength, split tensile strength and modulus of elasticity of concrete with a 0.4 fas using Styrofoam as a partial substitute for fine aggregate. The research method used is an experimental method by making the test object in the form of a concrete cylinder with a diameter of 15 cm and a height of 30 cm. The composition of the concrete mixture used is a volume ratio of 1 Pc: 2 Ps: 2 Kr with a fas 0.4. The styrofoam variations used are 10%, 20%, and 30% of the ratio to the volume of fine aggregate in normal concrete mixtures. Testing of the mechanical properties of concrete was carried out at the age of 7, 14, 21, and 28 days for the concrete compressive strength test, and 28 days for the split tensile strength of the concrete, and the modulus of elasticity. The results showed that the compressive strength of the concrete increased with the age of the concrete and the addition of the styrofoam variations with the exception of the 10% variation. For the split tensile strength test, there was an increase in line with the increase in the styrofoam variation, while the modulus of elasticity decreased at 10% variation against 0% variation and increased at 20% and 30% variation with 0% variation. Keywords: Concrete, Styrofoam, Variation.